ANALISIS PENERAPAN PRINSIP PERLINDUNGAN LANGSUNG DALAM PENYELENGGARAAN PENCATATAN CIPTAAN - Nurdahniar, Inda (Veritas et Justitia, 2016)
This article deals with the problem arising out of copyright registration system which oftentimes leads to copyright disputes. The author argues that this dispute arises out of the possible conflict between automatic protection principle and the existing copyright registration system. Therefore, the author suggests that, in the case of copyright ownership dispute, registration should not be perceived as absolute evidence. Treating registration as absolute proof will instead violate the automatic protection system. Instead, the author suggests that other factors, such as publication of copyright, understanding of individuality concept, originality standards etc., should be taken into consideration as well, when determining copyright ownership. Keywords:automatic protection principle, copyrights registration, publication, individuality concept  originality standard